Stability Study of SATER Models in a Dynamic Approach with Application - Khnsaa F. Hameed‏ Alazawey, Nihad S. Khalaf‏ Aljboori (Mathematical Statistician and Engineering Applications, 2023)
This paper related to provide stability conditions of Self-Exciting Threshold Autoregressive model. This stability will be presented by the method developed by developer of this model, as well as finding these conditions by dynamical technique method. Finally, we will apply these conditions in a dynamical technique to the historical weekly data when the market is closed of silver prices per ounce in dollars for the period from (1-january 2015 to 18 September 2022) with 401 observation. It was applied using MATLAB (R2022a) put at the end of the paper in the form (m.file).